PENGARUH MODEL PEMBELAJARAN INKUIRI TERBIMBING TERHADAP KEMAMPUAN MEMAHAMI KONSEP DAN MINAT BELAJAR SISWA KELAS VII DI SMP YAYASAN PERGURUAN KELUARGA PEMATANGSIANTAR - Inggrian, Pebila; Tridelpina Purba, Sumarny; Perayanti Sinaga, Dian (Program Studi Pendidikan Biologi, Fakultas Keguruan Dan Ilmu Pendidikan Universitas Simalungun, 2023)
This study aims to determine the effect of the guided inquiry model on students' conceptual understanding and learning interests. The population in this study were seventh-grade students of SMP Yayasan Perguruan Keluarga Pematangsiantar in the 2021/2022 academic year, consisting of three classes totaling 93 students. The research sample was taken using Cluster Random Sampling, obtaining class VII-2 as the experimental class and VII-3 as the control class, totaling 62 students. The instruments used in the study were questionnaires and tests. The data obtained were analyzed using ANOVA with a significance level of 5% (α = 0.05) using SPSS'21. The results of the hypothesis testing on conceptual understanding ability obtained F count = 15.60, while F table at the 4.001 level. Because F count > F table with a significance value of 0.000 <0.05, Ho is rejected and Ha is accepted. The results of the hypothesis testing on student learning interest obtained F count = 53.11, while F table 4.001. Because F count > F table with a significance value of 0.000 < 0.05, Ho is rejected and Ha is accepted. It was concluded that there is a significant effect of the guided inquiry learning model on students' conceptual understanding and learning interest in environmental pollution material for seventh-grade students at Yayasan Perguruan Keluarga Pematangsiantar Junior High School in the 2021/2022 academic year.